INTRODUCTION - Sterling, Gregory E. (The studia Philonica annual, 2021)
The corpus Philonicum is one of the largest bodies of non-Christian literature composed in Greek by a single author that has come down to us from the ancient world. Like so many of the other large collections, a significant number of Philo’s writings have been lost: approximately one-third of what Philo wrote has disappeared.¹ Just as there were attempts to organize or catalogue other large corpora in the ancient world such as the corpus Aristotelicum,² so Eusebius provided a catalogue of Philo’s works that were part of the Episcopal library in Caesarea. However, the bishop’s three categories of works that...